Effects of Symbiotic Fungi on Sugars and Soil Fertility and Structure-Mediated Changes in Plant Growth of Vicia villosa - Wan-Xia He; Qiang-Sheng Wu; Abeer Hashem; Elsayed Fathi Abd_Allah; Pandiyan Muthuramalingam; Al-Bandari Fahad Al-Arjani; Ying-Ning Zou (Agriculture, 2022)
Many terrestrial plants form reciprocal symbioses with beneficial fungi in roots; however, it is not clear whether Vicia villosa, an important forage and green manure crop, can co-exist with these fungi and how such symbiosis affects plant growth and soil properties. The aim of this study is to analyze the effects of inoculation with three arbuscular mycorrhizal fungi (AMF) such as Diversisporaspurca, Funneliformismosseae, and Rhizophagusintraradices and an endophytic fungus Serendipitaindica on plant growth, root morphology, chlorophyll and sugar levels, soil nutrients, and aggregate size distribution and stability in V. villosa plants. After 63 days of inoculation, the beneficial fungi colonized the roots with colonization rates of 12% to 92%, and also improved plant growth performance and root morphology to varying degrees, accompanied by the most significant promoted effects after R.intraradices inoculation. All AMF significantly raised chlorophylls a and b, carotenoids and total chlorophyll concentrations, along with a significant increase in leaf sucrose, which consequently formed a significantly higher accumulation of glucose and fructose in roots providing carbon sources for the symbionts. Root fungal colonization was significantly (p < 0.01) positively correlated with chlorophyll compositions, leaf sucrose, and root glucose. In addition, inoculation with symbiotic fungi appeared to trigger a significant decrease in soil Olsen-P and available K and a significant increase in NH4-N, NO3-N, and glomalin-related soil protein levels, plus a significant increase in the proportion of water-stable aggregates at the size of 0.5–4 mm as well as aggregate stability. This improvement in soil aggregates was significantly (p < 0.01) positively correlated with root fungal colonization rate and glomalin-related soil protein concentrations. The study concludes that symbiotic fungi, especially R. intraradices, improve the growth of V. villosa, which is associated with fungal modulation of sugars, soil fertility and root structural improvement.